2021
DOI: 10.1186/s12916-021-02013-5
|View full text |Cite
|
Sign up to set email alerts
|

A phenome-wide association study of genetically mimicked statins

Abstract: Background Beyond their success in cardiovascular disease prevention, statins are increasingly recognized to have sex-specific pleiotropic effects. To gain additional insight, we characterized associations of genetically mimicked statins across the phenotype sex-specifically. We also assessed whether any apparently non-lipid effects identified extended to genetically mimicking other widely used lipid modifiers (proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors and ezetimibe) or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 65 publications
(83 reference statements)
0
14
1
Order By: Relevance
“…Interestingly, despite extensive validation of the effects of HMGCR inhibition on cardiometabolic traits by previous studies [44,45], we observed HEIDI significance for the association of HMGCR expression in blood with CAD and LDL-C (Fig. 3), which suggested that the variant associated with HMGCR expression was distinct from those associated with CAD risk and LDL-C levels.…”
Section: Replication Of Analysis In Npc Cellscontrasting
confidence: 61%
“…Interestingly, despite extensive validation of the effects of HMGCR inhibition on cardiometabolic traits by previous studies [44,45], we observed HEIDI significance for the association of HMGCR expression in blood with CAD and LDL-C (Fig. 3), which suggested that the variant associated with HMGCR expression was distinct from those associated with CAD risk and LDL-C levels.…”
Section: Replication Of Analysis In Npc Cellscontrasting
confidence: 61%
“…Interestingly, we observed HEIDI significance for the association of HMGCR expression in blood with CAD and LDL-C (Figure 4), which suggested that the variant associated with HMGCR expression was distinct from those associated with CAD risk and LDL-C level, despite extensive validation of the effects of HMGCR inhibition on these traits by previous studies [43, 45]. The HEIDI significance may be due to the complex LD structures in the GWAS studies, which may not be accurately accounted for by the LD reference (Supplementary Figure 9).…”
Section: Resultsmentioning
confidence: 71%
“…We observed no association between HMGCR expression and inflammatory cytokine levels, namely IL6 and CRP. Interestingly, we observed HEIDI significance for the association of HMGCR expression in blood with CAD and LDL-C (Figure 2), which suggested that the variant associated with HMGCR expression was distinct from those associated with CAD risk and LDL-C level, despite extensive validation of the effects of HMGCR inhibition on these traits by previous studies (18,19). This is likely due to the complex LD structures in the GWAS studies (Supplementary Figure 11).…”
Section: Genetically Predicted Statin On-target and Off-target Inhibi...mentioning
confidence: 80%
See 1 more Smart Citation
“…Two interventional studies using statins have showed a reductions in calcium levels [45,46], whereas another single-arm study showed declines that did not reach significance [47]. A Mendelian Randomization approach using LDL-C as the instrument was also associated with elevated calcium levels [48], further supporting a potential causal relationship with cholesterol driving calcium levels. As this is a cross-sectional associative relationship we are not able at present to define directionality, much less the underlying biological mechanism(s).…”
Section: Discussionmentioning
confidence: 99%